WHAT MAKES THE CYBERBULLYING MODEL AMONG VOCATIONAL HIGH SCHOOL STUDENTS - Naila Nasywa; Fatwa Tentama; Mujidin Mujidin (Jurnal Cakrawala Pendidikan, 2021)
Cyberbullying refers to aggressive behaviors in social media in the forms of repeated actions of insults, shaming, and threats to other people. This study aims to examine the model of empathy, self-esteem, and school climate effects on cyberbullying to vocational students. The participants of this study were 505 eleventh grade students from vocational schools X, Y, and Z in Yogyakarta. The sample of this study included 180 students which were selected from the population using the cluster random sampling technique. Data were collected using the empathy, self-esteem, and school environment scales. The collected data were then analyzed using inner and outer model tests in Structural Equation Model (SEM) using Smart Partial Least Square 3.2.8. The results of this study show that the model with empathy, self-esteem, and school climate to predict cyberbullying had a good fit with the empirical data. It was found that empathy and school environment had a negative effect on cyberbullying. In contrast, no effects were found in self-esteem and cyberbullying.